Correction: Fabrication of free-standing membranes with tunable pore structures based on the combination of electrospinning and self-assembly of block copolymers. Issue 86 (1st December 2017) - Zhou, Meimei; Wu, Yi-nan; Luo, Pingping; Lyu, Jiqiang; Mu, Dengrui; Li, Aowen; Li, Fengting; Li, Guangtao
Abstract : Correction for 'Fabrication of free-standing membranes with tunable pore structures based on the combination of electrospinning and self-assembly of block copolymers' by Meimei Zhou et al., RSC Adv., 2017, 7, 49568–49575.